1984
DOI: 10.3109/00016348409156277
|View full text |Cite
|
Sign up to set email alerts
|

Serum Urate as a Predictor of Fetal Outcome in Severe Pre‐Eclampsia

Abstract: Maternal serum urate levels were studied in 50 normal pregnancies and 72 cases of severe pre-eclampsia. Markedly elevated levels of serum urate were found in severe pre-eclampsia, compared with normal pregnancy. In severe pre-eclampsia significantly higher levels were found prior to parturition in cases of growth retardation and perinatal distress, compared with patients whose newborns were of normal size and condition. Particularly high serum urate levels were found early in the third trimester in cases of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0
2

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 10 publications
4
28
0
2
Order By: Relevance
“…Several authors [1,3,4,5,6,7,10] have stated that hyperuricemia associated with a hypertensive pregnancy increases the incidence of intrauterine growth retardation, low birth weight and severe fetal distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors [1,3,4,5,6,7,10] have stated that hyperuricemia associated with a hypertensive pregnancy increases the incidence of intrauterine growth retardation, low birth weight and severe fetal distress.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism that produces this elevation of SUA concentration has not been clearly defined yet, but as SAGEN [6] and DUMONT [2] have suggested, it may result from increased blood lactate levels due to anaerobic metabolism of the uteroplacental unit. An increased SUA concentration may also be affected by impaired uric acid clearance caused by maternal hemoconcentration [4]The aim of our study was to analyze the possible correlation between the highest levels of SUA observed in hypertensive pregnant patients during the third trimester of gestation, the severity of PE and the perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Although hyperuricemia does correlate with maternal morbidity, there is an even stronger association of uric acid with the risk for small birth weight infants and with overall fetal mortality. 14,15 Nevertheless, whereas once viewed as a helpful marker to distinguish preeclampsia from the more benign forms of gestational hypertension, several recent studies have challenged the use of serum uric acid in predicting either preeclampsia or its myriad of complications. 16 -18 In this issue of Hypertension, Roberts et al 19 revisit the clinical use of serum uric acid as an aid in assessing the risk for adverse outcomes among women with hypertensive disorders of pregnancy.…”
mentioning
confidence: 99%
“…13 Whereas serum uric acid usually falls to levels well below 4 mg/dl during early-to-middle pregnancy, in patients with preeclampsia, levels often rise Ͼ4.5 mg/dl. 14,15 Several studies have correlated the rise in uric acid with the severity of the preeclamptic syndrome and with the degree of glomerular injury. 14,15 Although hyperuricemia does correlate with maternal morbidity, there is an even stronger association of uric acid with the risk for small birth weight infants and with overall fetal mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation